Influence of soil quality factors on capsaicin biosynthesis, pungency, yield, and produce quality of chili An insight on Csy1, Pun1, and Pun12 signaling responses - Das, Subhasish (Plant physiology and biochemistry : PPB, 2021)
Copyright © 2021 Elsevier Masson SAS. All rights reserved.